Numerical analysis of geometrical configuration effects on near-field shockwave propagation in CL-20 based underwater explosives - Ji-ping Chen; Jun Wang; Xian-pi Zhang; Yan-jie Zhao; Xing-xing Wu; Fang-zhou Zhu; Jun Yu (AIP Advances)
This study investigates how explosive charge configurations affect blast wave propagation during underwater detonations, focusing on transient multiphase flow interactions. The numerical methodology employs an advanced compressible multiphase flow simulation framework incorporating high-order weighted essentially non-oscillatory schemes, complemented by rigorous validation procedures involving comparative analyses against benchmark experimental data and analytical predictions from gas dynamics theory. The computational framework implements algorithmic initiation modeling for detonation processes, coupled with a front-tracking methodology employing the modified ghost fluid method to resolve discontinuities at immiscible phase boundaries. Comparative analysis of hydrodynamic simulations involving spherical and cylindrically configured CL-20 charges—a high-density polymorphic energetic compound—demonstrates that while both geometries exhibit comparable initiation energetics, cylindrical variants generate unique azimuthally asymmetric density distributions characterized by vortical flow structures. Quantitative evaluations reveal pronounced disparities in blast overpressure magnitudes between configurations at proximal standoff distances with observed variance attenuating exponentially in a petal shape as the propagation distance increases. These observations underscore the deterministic relationship between the explosive geometric topology and resultant fluidic shock phenomenology, providing critical insights for optimizing blast mitigation strategies in naval architecture and precision demolition engineering.